An Analysis Of 10th Grade High School Students’ Learning Approaches in the Context of EFL Online Learning - Luh Putu Shanti Yuliastiti; Made Hery Santosa; I Putu Ngurah Wage Myartawan (Journal of English Development, 2023)
The globalization and 21st century learning needs students to adopt a better approach to learning. As there are two types of approaches namely surface approach and deep approach, it is needed to investigate which are students leaning towards to, including the supporting and inhibiting factors that influence them especially in the sudden transition of online learning in pandemic situation. Using the modified R-SPQ-2F and a semi-guided interview, the study was conducted in one high school in North Bali. Using Slovin formula, there are 200 respondents who participated in the study. The modified R-SPQ-2F were analyzed using the mean score analysis and the results are students leaning towards the surface approach in the context of EFL Online learning. The interview analyzed with interactive model analysis gives comprehensive view of the supporting and inhibiting factors of the deeper approach. Turns out personal motivation, teachers’ style of teaching, and environmental factors directs their approach. These findings showed that the student learning approach is one way to evaluate the learning process. Teachers, students, and government should consider this to re-adjust the current learning situation to improve the quality of education.